Fear of Movement/(Re)Injury: An Update to Descriptive Review of the Related Measures - Liu, Haowei; Huang, Li; Yang, Zongqian; Li, Hansen; Wang, Zhenhuan; Peng, Li (Frontiers in Psychology, 2021)
The prevalence of fear of movement (kinesiophobia) in persistent pain ranges from 50% to 70%, and it may hinder the subsequent rehabilitation interventions. Therefore, the evaluation of fear of movement/(re)injury plays a crucial role in making clinical treatment decisions, conducive to the promotion of rehabilitation and prognosis. In the decision-making of pain treatment, the assessment of fear of movement/(re)injury is mainly completed by scale/questionnaire. Scale/questionnaire is the most widely-used instrument for measuring fear of movement/(re)injury in the decision-making of pain treatment. At present, the most commonly used scale/questionnaire are Tampa Scale for Kinesiophobia (TSK), Fear-avoidance Beliefs Questionnaire (FABQ), Kinesiophobia Causes Scale (KCS), Athlete Fear-avoidance Questionnaire (AFAQ), and Fear-avoidance Components Scale (FACS). In order to provide necessary tools and references for related research and rehabilitation treatment, this descriptive review is designed as an introduction about the background and content, score system, available language versions, variants of the original questionnaire, and psychometric properties.